ALIH FUNGSI RUMAH ADAT BATAK TOBA MENJADI HOMESTAY DI DESA LUMBAN SUHI SUHI KECAMATAN PANGURURAN SAMOSIR - Sinurat, Lamtiur L. H; Malau, Waston (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
The research aims to determine the function conversion factors, and the process of converting Toba Batak traditional houses into homestays in Lumban Suhi-suhi Village, Pangururan District, Samosir Regency. The type of research used is qualitative research with a descriptive approach. Data collection techniques were carried out using observation, interviews and documentation. The data that has been collected is analyzed through data reduction, data presentation, and drawing conclusions. The results of the research explain that the Toba Batak traditional house in Lumban Suhi-suhi Village has undergone a change in function from being a family residence to becoming more economically valuable. The factor in changing the function of a traditional house into a homestay is that there is an external factor in the form of encouragement from the Ministry of PUPR to revitalize the house into a residence for tourists based on community empowerment, then internal factors are also put forward in the form of the community's desire to improve the economy from house rental proceeds or from sales of local products to local residents. visitor. The function transfer process goes through various stages; 1) Location survey, 2) distribution of ideas, 3) deliberation, 4) data collection, 5) distribution of funds, 6) renovation, 7) training, 8) completing facilities, 9) opening, 10) marketing, 11) management.